HEMODYNAMIC AND METABOLIC STUDIES OF LEFT VENTRICULAR BYPASS WITH A CENTRIFUGAL BLOOD PUMP - YADA, I.; SAITO, K.; KUSAGAWA, M.; HATTORI, R.; MIYAMURA, K.; WEI, C. M. (Jinko Zoki, 1985)
We evaluated the effectiveness of a centrifugal left ventricular assist device in dogs with acute myocardial infarction and in unanesthetized goats with normal heart. Pulse pressure decreased half of normal at 50% and was gone nonpulsatile flow at 100% left ventricular bypass. RV output and renal blood flow increased following increasing left ventricular bypass flow. But carotid blood flow was no significant change. TTI reduction decreased in 25.6+11.2% at 50% and 52.3+21.3% at 100% LV bypass respectively. Serum cathecholamine levels and renal functions remained normal. These data indicate no untoward effects as a result of prolonged nonpulsatile perfusion.